Resiliensi Pendidikan Pesantren Salafiyah di Era Modern: Studi Kasus Pondok Pesantren Azzakariyyah Merangin Jambi: STUDI KASUS PONDOK PESANTREN AZZAKARIYYAH MERANGIN JAMBI - Adam Malik; Rehani; Muhammad Zalnur; Mukhlis (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
Salafiyah Islamic boarding schools, as traditional Islamic educational institutions, face various challenges in the modern era. Therefore, a balance between classical Islamic education and modern education is essential to remain sustainable, relevant, and competitive amidst modernization. This study aims to identify the resilience of the educational system at Pondok Pesantren Azzakariyyah Merangin Jambi. Employing a qualitative research design with a case study approach, the research findings reveal that integrating traditional and modern education is crucial for producing students who are well-versed in knowledge suited to the demands of the modern era. This is achieved through the preservation of traditional elements such as dormitories, mosques, yellow books, students, and scholars, as well as traditional teaching methods, which reflect a strong social capital in facing modernization challenges. Strategic initiatives such as establishing educational foundations, providing madrasah education, integrating knowledge, and revitalizing the pesantren have reinforced its role as a resilient educational institution. Traditional learning methods such as wetonan, sorogan, tahfidz, mudzakarah, and majlis ta'lim, supported by visionary leadership and management integrated with modern education, enable the pesantren to remain relevant with the times. Nevertheless, the pesantren still faces challenges such as limited financial resources, inadequate infrastructure, and other resources.